Polar bears as a sentinel for emerging wildlife zoonoses with implications for public health in Alaska, southern Beaufort Sea, (2007-2014) - Todd Atwood (Research Workspace, 2013)
This project analyzed serum and plasma samples from the southern Beaufort Sea polar bear population from 2007 to 2014 to determine the current and past prevalence of diseases (Brucella spp., C. burnetii, and T. gondii) and exposure to persistent organic pollutants (POPs). The data provided information on demographic characteristics of individual polar bears sampled, along with measured exposure to infectious agents and contaminants. The overarching objective of the study was to characterize patterns of exposure over time. Polar bears were captured on the sea ice from late March to early May, 2007-2014. Blood samples were collected and tested for antibodies to Brucella spp., C. burnetii, and T. gondii. The Brucella antigen card test and standard plate test were performed.